Pengembangan Bahan Ajar Digital Interaktif Berbantuan Adobe Flash Pada Mata Pelajaran Korespondensi Kelas X OTKP di SMK YPM 3 Taman - Rahmatun Nafidah; Bambang Suratman (Universitas Negeri Surabaya, 2020)
The development of digital interactive media assisted with adobe flash research is done to describe the result of the development of that media, its appropriateness which is observed based on the subject expert validator, graphics, language, and the responses of the students toward the media. This research is applied on the understanding basic competence of the office communication and applying communication using phone in Indonesia language as learning media for the students of tenth grade of OTKP 1 in YPM 3 Taman Vocational high school on correspondence subject. This thesis uses developments research (R&D) with the 4-D development model which is about 4 steps of research, they are Defining, arranging, developing, and spreading process. However, the subjects of this research are 20 students of tenth graders in YPM 3 Taman vocational high school. The result of this research shows that interactive digital media is absolutely suitable for teaching. It is 97% for material validation feasibility (very good), 97% for graphic feasibility (very good), 98% for language feasibility (excellent). The average of the result is 97,3%, which means excellent. While the result of the students response is 98,8%, which means excellently interpreted. Based on the result, it is concluded that the interactive digital media, assisted with adobe flash, on the correspondence subject is suitable and good for being applied as both a media and learning source for the students in teaching-learning process.